2018
DOI: 10.3389/fimmu.2018.01504
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Oligosaccharides Ameliorate Colon Cancer by Regulating Oxidative Stress- and Inflammation-Activated Signaling Pathways

Abstract: Colon cancer (CC) is the third common neoplasm worldwide, and it is still a big challenge for exploring new effective medicine for treating CC. Natural product promoting human health has become a hot topic and attracted many researchers recently. Pectin, a complex polysaccharide in plant cell wall, mainly consists of four major types of polysaccharides: homogalacturonan, xylogalacturonan, rhamnogalacturonan I and II, all of which can be degraded into various pectin oligosaccharides (POS) and may provide abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 146 publications
(144 reference statements)
0
35
1
Order By: Relevance
“…There are multiple reports that investigate the ameliorating effect of oligosaccharides, sugars, and proteoglycans on inflammation [15,[82][83][84][85][86]. However, there are just a few papers [87,88], that focus on their effect on other aspects of complex diseases such as UC and CD. In the present study, we demonstrated that the modulation of the host microflora by a monosaccharide fucose did not affect the severity of the chronic colitis in terms of the intestinal inflammatory response, but partially ameliorated the changes in metabolism and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple reports that investigate the ameliorating effect of oligosaccharides, sugars, and proteoglycans on inflammation [15,[82][83][84][85][86]. However, there are just a few papers [87,88], that focus on their effect on other aspects of complex diseases such as UC and CD. In the present study, we demonstrated that the modulation of the host microflora by a monosaccharide fucose did not affect the severity of the chronic colitis in terms of the intestinal inflammatory response, but partially ameliorated the changes in metabolism and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al . () successfully employed this strategy with hydrocolloids such as xanthan, carrageenan or locust bean gum to improve water holding capacity of dough and increase quality (e.g. cooking yield and firmness) of obtained cooked salt free noodles.…”
Section: Interactions Of Hydrocolloids and Related New Trendsmentioning
confidence: 99%
“…Furthermore, interactions (ionic and H-bonding) of gluten and starch in dough with different nonionic (guar gum, locust bean gum) and anionic (alginate, pectin, carrageenan, xhantan gum) hydrocolloids could be exploited to improve rheological, pasting or fermentation behaviours of the dough . Tan et al (2018a) successfully employed this strategy with hydrocolloids such as xanthan, carrageenan or locust bean gum to improve water holding capacity of dough and increase quality (e.g. cooking yield and firmness) of obtained cooked salt free noodles.…”
Section: Interactions Of Hydrocolloids and Related New Trendsmentioning
confidence: 99%
“…This property is also present in their oligomers, which also show a prebiotic activity that controls microbiota population in the gastrointestinal tract [9,26].A well-known heteropolysaccharide in vegetable and fruit peels is pectin. Its composition and structure are notably more complex than the ones of the other polysaccharides typically encountered in lignocellulosic biomass [27]. Linear regions conformed only by α-1,4 linked galacturonic acid are known as homogalacturonans, while there are other parts of pectin rich in rhamnose that are branched or hairy regions.…”
mentioning
confidence: 99%
“…Rhamnogalacturonan I contains a main chain of rhamnose and galacturonic acid with lateral chains of galactose and arabinose, with several types of bonds. Rhamnogalacturonan II can contain, apart from all those monomers previously mentioned, other rare ones as apiose and aceric acid [27]. Though pectin is a typical food ingredient for jellies, marmalades and jams, its slow degradation in the intestine permits its use with calcium salts to treat diarrhea, it can ameliorate diverse colon cancer, promoting gut health by controlling microbiota populations (a prebiotic effect) [27,28].…”
mentioning
confidence: 99%